INTELLECTUAL TREASURES OF ULAMA MANDAR TRACING THE DYNAMICS OF ISLAM NUSANTARA IN LAND OF MANDAR - Hannani Hannani; Muhammad Ismail; M. Ali Rusdi; Tamsil Tamsil (Al-Qalam, 2022)
The entry of Islam in Mandar is a phenomenon because Islam in Mandar entered in an extraordinary way without any rejection from the public in general and from the royal elite, besides that until now Mandar land is still an important reference in learning and deepening Islamic science, especially the learning of the Yellow Book (kitta’ kuning) in Sulawesi. This study explores how scholars spread Islamic teachings in Mandar and how scholars respond to the very diverse Local Culture of Mandar. In uncovering this, the study used Qualitative Descriptive methods in the form of observations, interviews and focus group discussions (FGD). The location of this study is in West Sulawesi by focusing on the villages of Pambusuang and Campalagian Polman. The results showed that Islam entered Mandar peacefully because the way and approach used by scholars in spreading Islam was very in accordance with the situation and conditions of mandar society at that time which was a believer in Animism and Dynamism. The scholars in addition to conveying the teachings of Islam with full policy also make the local culture as an approach in conveying islamic teachings so that Islam enters the community with calm and pleasure. The findings in this study will certainly be very useful in the current proselytizing context, considering that Islam is currently widely highlighted and labeled extreme because one of the causes is preachers who seem to impose their opinions and beliefs on others.